Application of tone repair skincare product in the improvement of sensitive skin: Based on a cohort study of 60 cases - Zhigang LIAO; Si WEN; Xuesong XIAN; Beiming WANG; Junrui GONG; Baihui ZHANG; Jinyin LIANG; Xiaoyan FU; Li YE (Pifu-xingbing zhenliaoxue zazhi, 2023)
Objective To explore the role of functional skincare products in improving sensitive skin. Methods A total of 60 subjects with sensitive skin were selected by lactic acid sting test and randomly divided into the treated and control groups, 30 subjects per group. The treated group used tone repair skincare product and the untreated group served as the controls. The improvements in skin hydration, transepidermal water loss, a* value, redness area, and investigators' and subjects' self-evaluation scores were compared between the two groups 2 hours and 28 days after the applications. Results Compared to the control group, 28-day applications of tone repair skincare product significantly improved lactic acid sting scores (Z=-2.83, P<0.05). The stratum corneum hydration levels were increased both 2 hours and 28 days after topical applications of the products. In contrast, transepidermal water loss rates were dramatically decreased after 28-day applications (P<0.05, vs. controls). Both a* value and proportion of redness area were markedly decreased 2 hours after application of the product (P<0.05 for both). However, no significant differences in a* value and proportion of redness area were observed between the treated and control groups after 28-day applications. The investigators' assessment showed significant improvements in sensitive skin symptoms and sign, such as dryness, scales, telangiectasia and skin tightness in the treatment group compared to the control group (P<0.05). Conclusions Functional skincare products can improve the skin barrier function, playing an important role in improving the physiological state of sensitive skin.